Perancangan dan Pembuatan Website E-commerce Petra Gamng Store - Alexandro Yamin Suwito; Silvia Rostianingsih; Justius Andjarwirawan (Jurnal Infra, 2015)
Petra Gaming Store is a hardware store which is engaged in the sale, purchase of mouse, keyboard, headset and mousepad based on forums such as kaskus. Petra Gaming Store want to create an e-commerce website that expected to expand the marketing area to face the competition in the forum.This website has a online ordering feature that allow users to make purchase and user can also keep track of any transaction that has been done. The user of the website is divided into two kinds of role, admin and user where admin is the seller who made the online store through website, while the user is the one who purchase product through website. This web developed and created using PHP, AJAX and JavaScript programming language for functions and appearance of the website. The program code made using notepad++ software tools.The data mining features using apriori algorithm which of these methods will analyze consumer habits to find the relationship between different products with shopping carts and the time of purchasing. Data that has been prepared will be processed according to the algorithm to produce frequent itemsets thath will generate association rules in table form. By using the output from data mining which of association rules and tables. By using online transaction, the process of ordering on Petra Gaming Store website is much easier than finding products on the forums or call.